Exploring the mechanism of Huanglian ointment in alleviating wound healing after anal fistula surgery through metabolomics and proteomics - Dongliang Zhang; Jiabo Gu; Yanyan Xu; Xiaowen Yu; Heiying Jin (Heliyon, 2024)
Anal fistula is a common anal and intestinal disease. The wound of anal fistula surgery is open and polluting, which is the most difficult to heal among all surgical incisions. To investigate the mechanism of Huanglian ointment (HLO) on wound healing after anal fistula incision. The S. aureus infected wound in SD rats were used to imitate poor healing wound after anal fistula surgery. SD rats with wound sites (n = 24) were randomly divided into four groups (Control group, Model group, Potassium permanganate (PP) treatment group, and HLO treatment group). The wound healing rate was evaluated, HE staining was used to evaluate the pathological changes of each group, ELISA was used to detect the secretion of inflammatory factors in each group, and the mechanism was explored through metabolomics and proteomics in plasma rat. Compared to other groups, the rate of wound healing in the HLO group was higher on days 7 and 14. Histological analysis showed that collagen and fibroblast in HLO rats were significantly increased, inflammatory cells were reduced, and vascular endothelial permeability was increased. ELISA results showed that the secretion of inflammatory factors in HLO rats was significantly lower. Significant proteins and metabolites were identified in the wound tissues of the infected rats and HLO-treated rats, which were mainly attributed to Cdc42, Ctnnb1, Actr2, Actr3, Arpc1b, Itgam, Itgb2, Cttn, Linoleic acid metabolism, d-Glutamine and d-glutamate metabolism, Phenylalanine, tyrosine and tryptophan biosynthesis, Phenylalanine metabolism, alpha-Linolenic acid metabolism, and Ascorbate and aldarate metabolism. In conclusion, this study showed that HLO can promote S. aureus infected wound healing, and the data provide a theoretical basis for the treatment of wounds after anal fistula surgery with HLO.